2023
DOI: 10.1200/jco.21.02929
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Molecular, Therapeutic, and Patient Factors on Outcome of Diffuse Low-Grade Glioma

Abstract: PURPOSE In patients with diffuse low-grade glioma (LGG), the extent of surgical tumor resection (EOR) has a controversial role, in part because a randomized clinical trial with different levels of EOR is not feasible. METHODS In a 20-year retrospective cohort of 392 patients with IDH-mutant grade 2 glioma, we analyzed the combined effects of volumetric EOR and molecular and clinical factors on overall survival (OS) and progression-free survival by recursive partitioning analysis. The OS results were validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 44 publications
3
42
0
Order By: Relevance
“…Maximal safe resection is defined as resecting as much tumor-infiltrated tissue as possible to improve survival while minimizing the risk of postoperative neurological deficits and retaining quality of life [ 2 , 25 , 26 , 27 ]. As mentioned, SpTR has recently been associated with improved overall survival (OS) for both LGG and GBM [ 2 , 28 ]; however, the survival advantage of these more aggressive resections is lost when patients have a postoperative deficit [ 8 , 9 , 10 ]. As such, significant efforts have been made to develop pre- and intra-operative methods for maximizing EOR.…”
Section: Maximizing Extent Of Resection Is the Standard Of Carementioning
confidence: 99%
“…Maximal safe resection is defined as resecting as much tumor-infiltrated tissue as possible to improve survival while minimizing the risk of postoperative neurological deficits and retaining quality of life [ 2 , 25 , 26 , 27 ]. As mentioned, SpTR has recently been associated with improved overall survival (OS) for both LGG and GBM [ 2 , 28 ]; however, the survival advantage of these more aggressive resections is lost when patients have a postoperative deficit [ 8 , 9 , 10 ]. As such, significant efforts have been made to develop pre- and intra-operative methods for maximizing EOR.…”
Section: Maximizing Extent Of Resection Is the Standard Of Carementioning
confidence: 99%
“…The extent of tumor resection is a significant factor in determining low-risk vs high-risk outcomes in grades 2 and 3 gliomas. Studies have demonstrated that PFS and OS benefit when comparing gross total resections with subtotal resections in low-grade gliomas . Worse performance status has similarly demonstrated an association with worse OS and PFS in patients with low-grade gliomas .…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…While Kinslow et al included age, sex, IDH variant status, 1p/19q codeletion status, chemotherapy, radiotherapy, and MGMT promoter methylation status as covariables, they failed to account for extent of resection or Karnofsky performance status, 2 well-established prognostic indicators . These data were missing from the MSK-IMPACT cohort; therefore, they were not included in the final analysis.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Hervey-Jumper et al 1 have written a timely paper about the management of low‐grade glioma (LGG) as recently redefined. The WHO publications on LGG in 2016 and 2021 2 have grouped LGG into more precise variants whose biological behavior is better known.…”
mentioning
confidence: 99%
“…The patients included in the analysis by Hervey-Jumper et al 1 are different from cases included in trials about chemotherapy for astrocytoma (Table 1). In the analysis by Hervey-Jumper et al, 1 all patients had astrocytoma IDH-mutant, all were resectable, and most had an extensive resection.…”
mentioning
confidence: 99%